2004
DOI: 10.1111/j.0909-8836.2004.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary cartilages of the neonatal rat: the femoral head and the mandibular condyle

Abstract: Primary and secondary cartilages differ in embryonic origin and in histological organization, and are generally considered to have a different mode of growth. However, few studies have directly compared the two types of cartilage of the same animal at the same age. Therefore, we analysed several histological and biochemical differences between secondary cartilage of the mandibular condyle and primary cartilage of the femoral head of 4-d-old rats. We evaluated the tissue organization, the level of DNA and glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 32 publications
0
50
0
3
Order By: Relevance
“…To understand basic cellular mechanisms underlying TMJ OA, we harvested primary MCCs. Because the mandibular condylar cartilage is distinct from knee hyaline articular cartilage, [3][4][5][6][7][8] we compared MCCs with HACs isolated from the knee joint. Our mRNA and protein profiling revealed that the two cell populations share overlaping gene/protein expression patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand basic cellular mechanisms underlying TMJ OA, we harvested primary MCCs. Because the mandibular condylar cartilage is distinct from knee hyaline articular cartilage, [3][4][5][6][7][8] we compared MCCs with HACs isolated from the knee joint. Our mRNA and protein profiling revealed that the two cell populations share overlaping gene/protein expression patterns.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that MCCs may contain a unique population of precursor cells that are most likely derived from the articular zone, which is present in the TMJ but not in the knee. 8 Therefore, the specialized nature of MCCs underscores the importance of using them specifically to study the TMJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of the skull is governed and influenced by a number of factors [7][8][9][10]. The morphology of the temporomandibular joint reflects the complex development of the entire skull.…”
Section: Introductionmentioning
confidence: 99%
“…The mandibular condyle is a major growth site and plays a significant role during mandibular development. Cartilage of the mandibular condyle provides regional adaptive growth, endochondral bone growth and a movable articulation [8,9]. Thus information on skull morphogenesis as a whole is a prerequisite for understanding growth process in the TMJ.…”
Section: Introductionmentioning
confidence: 99%